2007
DOI: 10.1007/s10567-007-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Models of Affectionate Versus Affectionless Control in Anxious Families: A Critical Examination Based on Observations of Parent–Child Interactions

Abstract: Psychosocial theories focused on the intrafamilial transmission of anxiety often concentrate on specific parenting behaviors that increase risk of anxiety disorders in children. Two such theories--affectionate versus affectionless control--both implicate parenting, although differently, in the pathogenesis of childhood anxiety. The present article reviews observational studies that focus on interactions between parents and children in anxious families in order to examine critically each of these two models. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 73 publications
2
26
0
Order By: Relevance
“…One factor known to affect children is parenting interactions (DiBartolo & Helt, 2007). Consistent with previous research, in observed interactions with their children, anxious mothers (from both the OCD and panic groups) were less promoting of psychological autonomy and less warm than healthy controls.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…One factor known to affect children is parenting interactions (DiBartolo & Helt, 2007). Consistent with previous research, in observed interactions with their children, anxious mothers (from both the OCD and panic groups) were less promoting of psychological autonomy and less warm than healthy controls.…”
Section: Discussionsupporting
confidence: 78%
“…A high level of parental 'expressed emotion' defined by emotional over-involvement or criticism has been related to anxiety disorders in the children of anxious or depressed parents (Hirshfeld, Biederman, Brody, & Faraone, 1997). Observational research examining parent-child interactions has indicated that parents with anxiety disorders may be less warm and promoting of children's psychological autonomy (DiBartolo & Helt, 2007;Ginsburg et al, 2004;Whaley, Pinto, & Sigman, 1999), although this may be more related to child than parental anxiety (Moore, Whaley, & Sigman, 2004). In non-clinical samples parental anxietydepression and over-control have been linked to child internalizing problems (Bayer, Sanson, & Hemphill, 2006), as has the extent to which parental anxiety is expressed to children (Gruner, Muris, & Merckelbach, 1999;Muris & Merckelbach, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent associations have been found between perceived parenting and major depression [14], anxiety disorders [57], and externalizing behavior [8]. These associations appear to be non-specific.…”
Section: Introductionmentioning
confidence: 83%
“…and a less consistent relationship between low parental warmth and anxiety-disordered children (see DiBartolo and Helt 2007;McLeod et al 2007;Rapee 1997). To explore the effect of type of dyad, the sample was divided into four groups, based on the panic status of the mother and the anxiety status of the child.…”
Section: Discussionmentioning
confidence: 99%